The relevance of fluorescence radiation in Cherenkov telescopes. (February 2019) - Arqueros, F.; Rosado, J.; Morcuende, D.; Contreras, J. L.
Abstract: Cherenkov telescopes are also sensitive to the atmospheric fluorescence produced by the extensive air showers. However this contribution is neglected by the reconstruction algorithms of imaging air Cherenkov telescopes IACTs and wide-angle Cherenkov detectors WACDs. In this paper we evaluate the fluorescence contamination in the Cherenkov signals from MC simulations in both kinds of Cherenkov telescopes and for some typical observational situations. Results for an observation level of 2200 m a.s.l. are shown. In addition, the feasibility and capabilities of IACTs working as fluorescence telescopes are discussed with the assistance of some geometrical calculations.